Strengthening Disaster-Resilient Villages Through Participatory Approaches: Policy Recommendations for Village Governments - Sunarto Sunarto; Heru Santoso Wahito Nugroho; Suparji Suparji; Teta Puji Rahayu; Sulikah Sulikah; Hery Sumasto; Khambali Khambali (Health Dynamics, 2025)
Village resilience is an important foundation in community-based disaster risk reduction efforts. This policy brief is prepared based on recommendations from the results of village resilience assessment research. The research as the basis for the policy brief was conducted in 30 Disaster Resilient Villages in Magetan Regency using the Participatory Action Research (PAR) method, which emphasizes active community involvement in the assessment process. The assessment was carried out by filling out a questionnaire from the National Disaster Management Agency (BNPB) containing 128 questions and covering five main aspects: basic services, regulations and policies, prevention and mitigation, emergency preparedness, and post-disaster recovery. The questionnaire was filled out through interviews and focus group discussions (FGD). The results showed that only around 20% of villages achieved the Main Disaster Resilient Village category. This shows the need for an increase in overall efforts made by the disaster resilient village forum together with the village government. Two main recommendations are proposed. First, strengthening the capacity of the Disaster Resilient Village Forum as the driving force for disaster risk management activities at the village level. This forum needs to be supported through training, facilitation, and strengthening its role in program planning and implementation. Second, the allocation of village funds needs to be increased by around 5–8% to fund activities such as disaster-resistant infrastructure development, disaster mitigation, capacity training, emergency response simulations, procurement of facilities and infrastructure, emergency response funds, and post-disaster recovery. The success of both recommendations is highly dependent on collaboration between local and village governments. Local governments need to support with clear regulations, technical assistance, and adequate budgets. Meanwhile, village governments need to include disaster risk reduction in development plans. This synergy will accelerate the realization of disaster-resilient villages.